The Use of Tutorial Video on YouTube as Alternative Media for Teaching Writing of Procedure Text - Asmira AS; Ummi Khaerati Syam; Maharida (FKIP Unismuh Makassar, 2023)
The objective of this research is to use tutorial videos to improve the students’ writing skills as ninth graders. In this study, students' understanding was focused on the content and organization forms. Pre-experimental is a research method with pre-test and post-test as research instruments. The population in this study were students in the ninth grade of SMP Muhammadiyah 10 Makassar. The researcher took one class, namely class IX, as a sample consisting of 18 students. The findings showed that the average results of pre-test and post-test scores increased students' average scores. The average pre-test score was 39 for content and 39 for organization. Following treatment, students' post-test average scores increased by 77 in terms of content and by 76,7 in terms of organization. Meanwhile, students' writing skills in the form of content improved by 97%. Then, 96.7% of students' writing skills improved in terms of organization. This is evidenced in the results of the significance test in finding writing skills focusing on the content with a t-test value of 16.81 > 2.110 and organization with a t-test of 30.95 > 2.110. It is used to determine the hypothesis that occurs in this study. The hypothesis (H0) which was declared insignificant was rejected and the hypothesis (H1) was accepted, because the results of the t-test value for both content (16.81) and organization (30.95) were greater than the t-table value (2.110).